Report on visioning workshop of the Banspal Bikas Mancha (Living Lab) supporting locally led climate action, Odisha, India - Paliya, Vaishnavi; Tripathy, Saswatik; Prusty, Kartik Chandra; Falk, Thomas; Chabay, Ilan (International Food Policy Research Institute, 2025)
This report documents a one-day Vision to Action workshop organized by Foundation for Ecological Security (FES) with support of International Food Policy Research Institute (IFPRI), held on August 18, 2025, in Banspal village, Keonjhar, Odisha. The workshop is convened as a foundation step towards establishing a Living Lab in Banspal and situated within the broader framework of the CGIAR Climate Action Science Program.